Science, technology and innovation culture - Chouteau, Marianne; Forest, Joelle; Nguyen, Celine (London ISTE Ltd Hoboken, NJ John Wiley & Sons, Inc., 2018)
We are facing unprecedented challenges today. For many of us, innovation would be our last hope. But how can it be done' Is it enough to bet on the scientific culture' How can technical culture contribute to innovation' How is technical culture situated with regards to what we name collectively the culture of innovation' It is these questions that this book intends to address.
A Brief History of European Technical Culture and Its Relationship with Innovation / Anne-Fran?coise Gar?con -- When Innovation Culture Hides Technical Culture / Marianne Chouteau, Jo?elle Forest, C?eline Nguyen -- Technical Culture and the Contemporary World / Bruno Jacomy -- Industrialist and Inventor: Alfred Nobel's Dynamite Invention / Sophie Boutillier -- Thinking Creatively to Innovate: A Study of the Genesis of a Mathematical Breakthrough by C?edric Villani / Jo?elle Forest, Marie-Line Gardes, Dani?ele Vial -- Innovation Culture in Organizations / Muriel Davies, St?ephanie Buisine -- Technical Culture and Innovation Culture: Reconciling through Design / John Didier -- Cultural Anthropology, Animism, and Industrial Innovation Processes: The Case of the "Animal Language" Myth / Fanny Parise -- Conclusion -- List of Authors -- Index -- Other titles from iSTE in Innovation, Entrepreneurship and Management.
Prof. Nazareno (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Technological innovations; Corporate culture